Health behaviours associated with video gaming in adolescent men: a cross-sectional population-based MOPO study - Tuulia Puolitaival; Mirjam Sieppi; Riitta Pyky; Heidi Enwald; Raija Korpelainen; Marjukka Nurkkala (BMC, 2020)
Abstract Background Playing video games, a form of sedentary behaviour, is associated with poor well-being and increased risk of morbidity due to chronic disease. However, the association between health behaviours and video gaming is poorly understood. The purpose of this population-based study was to reveal the differences in dietary habits and physical activity for adolescent men with high amount of video games on weekdays, as compared to their peers who play less often. Methods Seven hundred ninety-six adolescent men (age: mean = 17.8, SD = 0.6) attended compulsory conscription for military service in 2013 and completed a questionnaire regarding the amount and frequency of their video gaming. They also participated in a medical examination and underwent physiological measurements. The participants who played video games more than 3 h/d on weekdays were compared with those who played 3h/d or less. The association between health behaviours and the amount of playing video gaming was analysed using multivariable logistic regression analysis. Results 24.1% (n = 192) of the participants reported video gaming in excess of 3 h/d. This group had higher incidence of having low physical fitness, having poor eating habits, and being obese. No differences were found in smoking or alcohol drinking habits. Other factors, including low leisure-time physical activity (OR = 1.94; 95% CI, 1.29-2.91), low consumption of vegetables and fruits (OR = 0.83; 95% CI, 0.72-0.97), high consumption of sweetened soft drinks (OR = 1.28; 95% CI, 1.06-1.55) and high amount of sitting time (OR = 1.40; 95% CI, 1.28-1.52), explained one-fourth of the difference. Conclusion In this population-based study, adolescent men who played video games a lot on weekdays had lower physical fitness, were more often obese, and had poorer dietary habits, as compared to their peers who played less often. Because playing video games typically adds to a person's total sedentary time, this activity may be associated with adverse health outcomes at a very young age- especially in combination with poor health behaviours. The results of this study can be utilized to promote health interventions targeted at adolescent men so as to raise their awareness of the disadvantages of excessive video gaming.